2016
DOI: 10.1021/acs.chemmater.6b00154
|View full text |Cite
|
Sign up to set email alerts
|

Diazaisoindigo-Based Polymers with High-Performance Charge-Transport Properties: From Computational Screening to Experimental Characterization

Abstract: One of the major challenges confronting organic electronics is the development of high-mobility semiconducting materials, especially n-channel and ambipolar semiconductors. Solution-processable semiconducting polymers have attracted much attention because of their tunable properties and their suitability for the fabrication of large-scale devices. Aza substitution has proven effective in electron-transport small-molecule semiconductors; however, high-performance polymeric semiconductors prepared by aza substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
130
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 119 publications
(136 citation statements)
references
References 56 publications
2
130
1
3
Order By: Relevance
“…N atom of pyridine functions as an electron‐accepting unit owing to its electronegative property. Huang et al exploited computational screening to predict that the azaisoindigo with 7,7′‐substitution was the best monomer ( Figure a) . This derivative displayed augmenting electron‐deficient characteristics, minimized dihedral angles, better coplanarity and hence elevated charge transport, which resulted in ambipolar behavior (2.33/0.78 cm 2 V −1 s −1 for holes/electrons) with bottom‐contact/top‐gate structure under air atmosphere (Figure b).…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…N atom of pyridine functions as an electron‐accepting unit owing to its electronegative property. Huang et al exploited computational screening to predict that the azaisoindigo with 7,7′‐substitution was the best monomer ( Figure a) . This derivative displayed augmenting electron‐deficient characteristics, minimized dihedral angles, better coplanarity and hence elevated charge transport, which resulted in ambipolar behavior (2.33/0.78 cm 2 V −1 s −1 for holes/electrons) with bottom‐contact/top‐gate structure under air atmosphere (Figure b).…”
Section: Ambipolar Organic Semiconducting Materialsmentioning
confidence: 99%
“…de Miguel et al. reported the synthesis and characterization of 7,7′‐diazaisoindigo, and two separate research groups incorporated this structure into donor‐acceptor polymers . Huang et al.…”
Section: Isoindigo Derivativesmentioning
confidence: 99%
“…Huang et al. reported a copolymer of diazaisoindigo and bithiophene ( 20 ) (Chart 3), which exhibited high and balanced hole and electron mobilities (Table ) . Following this, the group went on to synthesize a series of diazaisoindigo copolymers with biselenophene ( 21 ), thienothiophene ( 22 ), dithienylethene ( 23 ), and diselenophenylethene ( 24 ) donor units (Chart 3) .…”
Section: Isoindigo Derivativesmentioning
confidence: 99%
“…The optimized geometry of 2DPP is completely coplanar with a dihedral angle (ϕ) between adjacent thiophenes of two DPPs being 0.4°, which is much smaller than that of bithiophene (5.6°). Enhanced planarity not only extends the effective conjugation but also promotes π–π stacking which is favorable for improving efficient intramolecular as well as intermolecular charge transport . Meanwhile, 2DPP exhibits a much lower LUMO energy level (−2.97 eV) than that of mono‐DPP (−2.51 eV), indicating that 2DPP is a more electron‐deficient building block.…”
mentioning
confidence: 99%
“…Notably, the calculated LUMO energy levels of P2DPPs range from −3.17 to −3.13 eV, which are lowered by up to 0.09 eV compared to those of PDPPs (−3.12 to −3.04 eV). A low‐lying LUMO is an essential prerequisite for suppressing the chemical reactions that create electron traps for ambipolar charge transport . For P2DPP‐BT, P2DPP‐TT, and P2DPP‐TVT, it is found that the HOMO and LUMO wave functions are extensively delocalized over the entire conjugated backbone (Figure S5, Supporting Information), whereas the densities of the states for HOMO and LUMO of P2DPP‐BDT are mainly distributed on the 2DPP core due to the bad conjugation of BDT donor …”
mentioning
confidence: 99%